2013
DOI: 10.1016/j.jmb.2013.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Malachite Green Mediates Homodimerization of Antibody VL Domains to Form a Fluorescent Ternary Complex with Singular Symmetric Interfaces

Abstract: We report that a symmetric small molecule ligand mediates the assembly of antibody light chain variable domains (VLs) into a correspondent symmetric ternary complex with novel interfaces. The L5* Fluorogen Activating Protein (FAP) is a VL domain that binds malachite green dye (MG) to activate intense fluorescence. Crystallography of liganded L5* reveals a 2:1 protein:ligand complex with inclusive C2 symmetry, where MG is almost entirely encapsulated between an antiparallel arrangement of the two VL domains. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
125
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(134 citation statements)
references
References 82 publications
6
125
0
Order By: Relevance
“…Incidentally, the lower observed signal may be attributed to the protein-binding pocket encapsulating and shielding the fluorogen from background activation when free in solution. A similar observation was previously identified when measuring the photoinsulating properties of scFv scaffolds and cognate fluorogens (Saurabh et al, 2015;Szent-Gyorgyi et al, 2013). Thus, here, we find that HL1.0.1-TO1 lacks the ability to stabilize a twisted conformation into a planar geometry for fluorescence activation.…”
Section: Introductionsupporting
confidence: 89%
“…Incidentally, the lower observed signal may be attributed to the protein-binding pocket encapsulating and shielding the fluorogen from background activation when free in solution. A similar observation was previously identified when measuring the photoinsulating properties of scFv scaffolds and cognate fluorogens (Saurabh et al, 2015;Szent-Gyorgyi et al, 2013). Thus, here, we find that HL1.0.1-TO1 lacks the ability to stabilize a twisted conformation into a planar geometry for fluorescence activation.…”
Section: Introductionsupporting
confidence: 89%
“…Compared to conventional fluorescent reporters, MG-dL5 has enhanced photo-stability. The FAP protects the fluorogen from oxidative damage as crystallographic studies show that a single MG molecule is flanked by two L5 domains [35]. This feature was exploited here to monitor the stability of the IgG binding sites, as pAG MG would escape from the film matrix to become non-fluorescent.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to free MG, thefluorescenceofdL5-boundMGisenhanced by up to 20,000 folds, due to constraining of the rotatable bonds in MG by two L5 proteins. Crystallographic studies have shown that MG mediates dimerization of two L5 proteins to form a fluorescent ternary complex [35]. We hypothesized that the system of MG-conjugated pAG (pAG MG ), dL5_EAK and EAK16-II, when deployed together (called dL5 film), serves as a self-illuminating, injectable formulation for local deposition of IgG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The light chain of HL9-MG was previously found sufficient for fluorogen activation (33). Studies of similar light chain-only FAPs have shown that the assembled fluoromodule contains 1 fluorogen molecule bound between 2 light chains and that tethering of 2 light chains by a flexible linker increases binding affinity (28,34). A gene encoding a peptide-linked dimer of light chains from HL9-MG was generated, randomly mutagenized, and screened using a yeast expression system and cell sorting in hopes of finding clones with improved binding and fluorescence activation of a membrane-permeant MG derivative, MG-ester.…”
Section: Introductionmentioning
confidence: 99%